2007
DOI: 10.1017/s0025315407054999
|View full text |Cite
|
Sign up to set email alerts
|

Observations of rough-toothed dolphins (Steno bredanensis) off the coast of Utila, Honduras

Abstract: Local dive shop operators and fishermen report that rough-toothed dolphins (Steno bredanensis) are frequently encountered off the coast of Utila, Honduras, (16°05'46.5"N 86°55'47.8"W). Our observations suggest that at least some of these animals may constitute a resident population, although the extent of the resident group's home range has not been determined. Twenty-eight rough-toothed dolphins were identified using photo-identification techniques, 15 of which were re-sighted on two or more occasions. The 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…However, they are also known to use near-shore waters (within a few nautical miles) especially near oceanic islands, in areas of steep bathymetric relief (Gannier and West, 2005;Nekoba-Dutertre et al, 1999;Poole, 1993;Ritter, 2002). Although their pelagic habitat could suggest a nomadic way of life, several studies based on photo-identification have shown high levels of re-sightings, suggesting the presence of resident populations around islands Johnston et al, 2008;Kuczaj and Yeiter, 2007;Mayr and Ritter, 2005;Nekoba-Dutertre et al, 1999). In addition to site fidelity, limited dispersal was also found between two populations of rough-toothed dolphins around the island of Hawai'i and Ni'ihau/Kaua'i (Baird et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…However, they are also known to use near-shore waters (within a few nautical miles) especially near oceanic islands, in areas of steep bathymetric relief (Gannier and West, 2005;Nekoba-Dutertre et al, 1999;Poole, 1993;Ritter, 2002). Although their pelagic habitat could suggest a nomadic way of life, several studies based on photo-identification have shown high levels of re-sightings, suggesting the presence of resident populations around islands Johnston et al, 2008;Kuczaj and Yeiter, 2007;Mayr and Ritter, 2005;Nekoba-Dutertre et al, 1999). In addition to site fidelity, limited dispersal was also found between two populations of rough-toothed dolphins around the island of Hawai'i and Ni'ihau/Kaua'i (Baird et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…We know that they have a very large brain-to-body ratio, and the few that have been kept in captivity have been noted to be extremely flexible behaviorally (i.e., intelligent), with evidence for sophisticated second order learning (also called deutero-learning), which implies thought (Pryor et al 1969). Recent work (Kuczaj and Yeater 2007) indicates that they have tight social bonds with long-term relationships.…”
Section: Rough-toothed Dolphinmentioning
confidence: 99%
“…The rough-toothed dolphin is often regarded as an offshore species that prefers deep waters; however, it can occur in waters with variable bottom depths (e.g., Gannier and West, 2005;Kuczaj et al, 2007). It rarely occurs close to land, except around islands with steep drop-offs nearshore (Mignucci-Giannoni, 1998;Gannier, 2000;Ritter, 2002;Gannier and West, 2005;Kuczaj et al, 2007).…”
Section: Rough-toothed Dolphin (Steno Bredanensis)mentioning
confidence: 99%
“…It rarely occurs close to land, except around islands with steep drop-offs nearshore (Mignucci-Giannoni, 1998;Gannier, 2000;Ritter, 2002;Gannier and West, 2005;Kuczaj et al, 2007).…”
Section: Rough-toothed Dolphin (Steno Bredanensis)mentioning
confidence: 99%